Reading Surabaya at Close Range: Port Underworlds and Revolutionary Memory in Eko Darmoko’s Fiction - Rane, Zakridatul Agusmaniar; Aji, Rojil Nugroho Bayu (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2026)
This article reads Surabaya at close range through two Eko Darmoko’s short stories, examining how anomalous details and named urban sites disclose port commerce, revolutionary memory, and continuities and breaks between early maritime violence and the conflicts around 1945. Rather than treating Surabaya as a fixed historical background, this article approaches the city as a literary construction shaped by objects, places, affect, and narrative irregularities. This study is primarily a literary analysis that combines close reading with selective contextual triangulation. The analysis focuses on textual details in two short stories, including narrative anomalies, micro-topographies, focalization, material objects, and affective registers. Secondary materials (paratexts, port toponymy, cartographic references, scholarly articles, theses, and relevant historical documents) are used to clarify urban, historical, and cultural contexts of Surabaya. Each textual clue is read in relation to external traces and tested across scene, community, and city levels, without treating fiction as a substitute for historical documentation. Nusantara Abad 16 foregrounds port underworlds, counterfeit authority, coercive exchange, and gendered vulnerability. Cinta Absurd di Sekitar Yamato dan Kematian Mallaby organizes revolutionary memory through crowds, rumor, mobile perception, and volatile objects. Across both texts, coercive infrastructures persist, while commodity logics and authority forms shift. Quays, alleys, hotel thresholds, and bridges mediate agency. This article offers a literary microhistorical reading that keeps historical claims proportional to textual evidence. It contributes to Indonesian literary criticism, Surabaya studies, and debates on fiction, space, and urban historical imagination.